A Narrative Review of Recent Studies on the Role of Vitamin D in the Prevention of Cardiac and Renal Risk and Additional Considerations for COVID-19 Vulnerability - Panteli, Aikaterini E.; Theofilis, Panagiotis; Vordoni, Aikaterini; Vlachopanos, Georgios; Koukoulaki, Maria; Kalaitzidis, Rigas G. (Current Vascular Pharmacology, 2022)
The role of vitamin D in maintaining a healthy cardiovascular (CV) and the renal system has received increasing attention. Low vitamin D levels are associated with the incidence of hypertension, cardiac remodeling, and chronic congestive heart failure. Low vitamin D levels also influence renal disease progression and albuminuria deterioration. Moreover, recent research indicates that vitamin D deficiency can be a potential risk factor for coronavirus disease-19 (COVID-19) infection and poorer outcomes. Data are inconclusive as to whether supplementation with vitamin D agents reduces CV disease risk or COVID-19 severity. Conversely, in patients with kidney disease, vitamin D supplementation is associated with an improvement in kidney function and albuminuria. This narrative review considers recent data on the effects of vitamin D on the CV and renal system, as well as its possible role regarding COVID-19 complications.
Keywords: COVID-19